Ketimpangan Gender dan Kesehatan Sebagai Penentu Pertumbuhan Ekonomi Wilayah : Studi Data Panel Provinsi Jawa Timur 2017-2023 - Mahreza Radityo Ariphadayu; Nur Hidayah (Universitas Pendidikan Ganesha, 2025)
East Java, one of the provinces with the third largest economic contribution in Indonesia, has enormous potential to drive growth in the eastern region of the country. The purpose of this study is to determine and analyze how East Java's economic growth from 2017 to 2023 is influenced by life expectancy, the human development index, the labor force participation rate, and the gender inequality index. This study uses an econometric methodology and is quantitative. Panel data regression analysis is the data analysis technique used in this study. GDP is significantly negatively influenced by the Gender Inequality Index (GNI), positively by Life Expectancy (AHH), and positively by the Human Development Index (HDI) and the Labor Force Participation Rate (LFPR), while the latter two have positive coefficients. The variables GNI, HDI, LFPR, and LFPR influence GDP by 79.89%. The East Java regional government needs to strengthen gender mainstreaming policies by developing regulations that support equal access for women and men in education, employment, and economic participation.